State Liability for the Psychic of Death Row Inmates in the Implementation of the Waiting Period for Execution - Aranggraeni, Renda; Taufik, Moh.; Fausta, Moza; Ilmi, Moch Bakhrul (Electronic Journal of Education, Social Economics and Technology, 2024)
This research aims to analyze legal certainty in the implementation of standardization of the death penalty execution mechanism and examine the state's responsibility towards the psychological condition of death convicts during the waiting period for execution. The research method used is a normative juridical approach by analyzing laws and regulations, court decisions, and case studies related to implementing death penalty executions in Indonesia. The results showed that the absence of clear standardization in the mechanism of death penalty execution has the potential to cause legal uncertainty, both for law enforcement officials and for convicts. In addition, the prolonged waiting period for execution causes a significant psychological impact, which can be categorized as a form of psychological torture. The state has the responsibility to ensure the protection of the human rights of people sentenced to death, including by ensuring that the execution process is fair and does not unnecessarily prolong their psychological suffering. Therefore, firmer regulations are needed in standardizing the mechanism for carrying out death penalty executions to ensure legal certainty, as well as more humanist policies in handling the psychological conditions of death row inmates during the execution waiting period.